2017
DOI: 10.1177/0898756417731775
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Complete Blood Count Indices (NLR, PLR, MPV/PLT, and PLCRi) in Healthy Dogs, Dogs With Periodontitis, and Dogs With Oropharyngeal Tumors as Potential Biomarkers of Systemic Inflammatory Response

Abstract: The aim of the study was to retrospectively assess complete blood count (CBC) indices of dogs with periodontitis (PD; n = 73) and dogs with oropharyngeal tumors (OT; n = 92) in comparison to CBC indices of healthy dogs (HD; n = 71). Neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio, mean platelet volume to platelet ratio, and platelet large cell ratio index (PLCRi) were evaluated as biomarkers of systemic inflammatory response provoked by PD and OT. Results of multivariable polytomous logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 75 publications
(111 reference statements)
4
50
1
Order By: Relevance
“…In two further studies focusing on canine mast cell tumour, higher NLR was predictive of higher tumour grade and was correlated with poorer outcome in univariate analysis, although it was not confirmed as an independent prognostic factor for survival in multivariate analysis . Neutrophilia has also been linked with tumour‐associated systemic inflammatory response for different canine malignancies, such as oropharyngeal cancer and acute leukaemia . In a paper evaluating the prevalence of leukocyte populations in healthy, older and tumour‐bearing dogs, the authors reported that tumour‐bearing dogs had a higher number of WBC and a higher percentage of neutrophils .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In two further studies focusing on canine mast cell tumour, higher NLR was predictive of higher tumour grade and was correlated with poorer outcome in univariate analysis, although it was not confirmed as an independent prognostic factor for survival in multivariate analysis . Neutrophilia has also been linked with tumour‐associated systemic inflammatory response for different canine malignancies, such as oropharyngeal cancer and acute leukaemia . In a paper evaluating the prevalence of leukocyte populations in healthy, older and tumour‐bearing dogs, the authors reported that tumour‐bearing dogs had a higher number of WBC and a higher percentage of neutrophils .…”
Section: Discussionmentioning
confidence: 99%
“…29,31 Neutrophilia has also been linked with tumour-associated systemic inflammatory response for different canine malignancies, such as oropharyngeal cancer and acute leukaemia. 24,42 In a paper evaluating the prevalence of leukocyte populations in healthy, older and tumour-bearing dogs, the authors reported that tumour-bearing dogs had a higher number of WBC and a higher percentage of neutrophils. 43 Such findings are consistent with the results in this study.…”
Section: Eightymentioning
confidence: 99%
See 2 more Smart Citations
“…Neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), and mean platelet volume (MPV) are the most used in the literature [4][5][6]. Elevated NLR has reportedly been associated with poor survival following resection or chemotherapy in a variety of cancer.…”
Section: Introductionmentioning
confidence: 99%